Predation event of the Yucatan neotropical rattlesnake Crotalus tzabcan (Squamata: Viperidae) on a rodent, in southern Quintana Roo, Mexico - José Rogelio Cedeño-Vázquez; Pablo M Beutelspacher-García; Rubén Alonso Carbajal-Márquez (Novitates Caribaea, 2025)
The Yucatan neotropical rattlesnake (Crotalus tzabcan) is a crotalid endemic to the Yucatan Peninsula. Although it is widely distributed in this region, it is considered a highly elusive species, thus knowledge about its natural history is scarce, including observations on feeding ecology. Here, we report the first documented observation of a predation event of a wild C. tzabcan on a rat in a rural area in southern Quintana Roo, Mexico.